Regaining focus: Promoting attentional literacy in digital higher education - Palalas, Agnieszka; Pegrum, Mark; Dell, Debra (Australasian Journal of Educational Technology, 2024)
The attentional demands placed on digital learners have grown, with online and blended education increasingly impacted by hyperconnectivity and digital disarray. In this context, it is essential for educators to help learners develop attentional literacy (AL). Building on past research on AL which fused insights from the fields of digital literacies and contemplative pedagogy (CP), this Delphi study examined the concept of AL and associated practices in higher education. Starting with a working definition of AL, expert feedback was invited from a global panel of experienced CP practitioners across academic disciplines. Through three Delphi rounds, the AL definition was validated and refined, before an abbreviated version was produced to facilitate operationalisation by digital educators who may not have a CP background. The study further explored how AL can be integrated into online higher education curricula, identifying strategies for educators and students to develop AL practices and address barriers to these practices. Despite systemic and structural constraints, cultivating AL allows educators and students to exercise a greater degree of individual and collective agency over their own attention in a digital world. Implications for practice or policy: Students can be guided in developing AL through a series of stages involving awareness and noticing, focus and intentional choice, openness and curiosity, and consideration of the wider attentional ecosystem. Educators should develop their own AL first, approaching it holistically by integrating personal, pedagogical and professional development-related practices, along with complementary offline activities. Institutions can maximise scope for AL development by increasing technological support and, especially, reducing curricular time pressure on educators and students.